Exploration of Physical–Chemical and Structural-Phase Mechanisms in Ti-Al Intermetallic Coating Formation - Almaz Nazarov; Rustem Nagimov; Alexey Oleinik; Alexey Maslov; Alexey Nikolaev; Kamil Ramazanov; Vladimir Denisov; Yuri Ivanov; Elena Korznikova (Quantum Beam Science)
This study examines coatings based on Ti-Al system intermetallics deposited in a nitrogen environment. The research investigates the structure, phase composition, chemical composition, and mechanical properties of coatings with varying ratios of Ti-Al to TiAlN layer thicknesses. Multiple analytical techniques, including nanoindentation, sclerometry, microhardness measurements, electron microscopy, X-ray diffractometry, and transmission electron microscopy, were employed. The results demonstrate that the coating architecture significantly influences its physical and mechanical properties. Notably, coatings with a variable thickness gradient structure exhibit the best properties and are the most promising for practical applications, offering enhanced hardness, wear resistance, and adhesion strength. Furthermore, the findings indicate that a carefully selected combination of layers can be used to control coating properties across a wide range, making these coatings highly suitable for demanding industrial applications.